2006
DOI: 10.1258/135581906775094280
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and economics: does programme budgeting and marginal analysis contribute to fair priority setting?

Abstract: There is potential for combining A4R and PBMA in a more comprehensive approach to priority setting, which uses a fair priority-setting process to reach decisions aimed at achieving optimal benefits with available resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 14 publications
4
61
0
2
Order By: Relevance
“…use of the formal priority setting approach known as PBmA has been shown in other contexts to make decision-makers more aware of the ethical issues involved in allocating scarce resources (e.g., see Gibson et al 2006). In some cases, as shown in our findings, this awareness may lead to moral distress.…”
Section: Discussionmentioning
confidence: 61%
“…use of the formal priority setting approach known as PBmA has been shown in other contexts to make decision-makers more aware of the ethical issues involved in allocating scarce resources (e.g., see Gibson et al 2006). In some cases, as shown in our findings, this awareness may lead to moral distress.…”
Section: Discussionmentioning
confidence: 61%
“…The use of evidence in priority setting was more prominent in the HICs ( Gibson et al ., 2006; Goodwin & Frew, 2013; Menon et al ., 2007; Robinson et al ., 2012) than the LMICs. This was because priority setting in LMICs was characterized by historical allocations and subjective considerations ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the papers attributed the failure to meet this condition to constant failure by decision makers to provide rationale for decisions made ( Bravo Vergel & Ferguson, 2006; Bukachi et al ., 2014; Gibson et al ., 2006; Maluka et al ., 2010a; Zulu et al ., 2014). For example, Bravo Vergel & Ferguson (2006), observed that though the primary care trusts in England made some effort to communicate priority setting policies through general practitioners and in some few instances through flowcharts and leaflets, the provision of rationale for the decisions were never given.…”
Section: Resultsmentioning
confidence: 99%
“…*2 Baltussen et al, 2007;Defechereux et al, 2012;Duthie et al, 1999;Golan & Hansen, 2010;Venhorst et al, 2014;Youngkong et al, 2009. *3 Dionne et al, 2015Dolan, 2010;Duthie et al, 1999;Le Gales & Moatti, 1990;Gibson et al, 2006;Gurtner, 2014;Hilgerink et al, 2011;Johnson et al, 2009;Lasry et al, 2011;Mullen, 2004;Ritrovato et al, 2015;Tannahill, 2008;Wilson et al, 2006;Wilson et al, 2007;Youngkong et al, 2012a;Youngkong et al, 2012b. *4 de Greef-van der Sandt et al, 2016;Vuorenkoski et al, 2008;Youngkong et al, 2009. *5 Diaby & Goeree , 2014Goetghebeur et al, 2008;Goetghebeur et al, 2010;Goetghebeur et al, 2012;Golan & Hansen, 2010;Hailey, 2009;Menon et al, 2010;Miot et al, 2012;Mullen, 2004;Tony et al, 2011;University of York, 2002;Wilson et al, 2007. *6 Golan & Hansen, 2010;Johnson et al, 2009;Martin et al, 2001;Meagher, 2010;Noorani et al, 2007;Simoens, 2014;V...…”
Section: (("Decision Making"[mesh] Not Shar*[tiab]) or ("Decision Supunclassified
“…*30 Andreae et al, 2009;Baltussen et al, 2007;Defechereux et al, 2012;Diaby & Goeree, 2014;Diaby & Lachaine, 2011;Ghaffar, 2009;Gibson et al, 2006;Goetghebeur et al, 2008;Goetghebeur et al, 2010;Goetghebeur et al, 2012;Gurtner, 2014;Hailey, 2009;Jehu-Appiah et al, 2008;Kolasa et al, 2016;Koopmanschap et al, 2010;Lasry et al, 2011;Lopert, 2009;Menon et al, 2010;Miot et al, 2012;Mullen, 2004;Tannahill, 2008;Thokala & Duenas, 2012;Tony et al, 2011;University of York, 2002;Venhorst et al, 2014;Youngkong et al, 2009;Youngkong et al, 2012a. *31 Andreae et al, 2009;Lasry et al, 2011;Lopert, 2009;Youngkong et al, 2009. *32 Dionne et al, 2009;Golan & Hansen, 2010;Johnson et al, 2009;Kirby et al, 2008;Mullen, 2004. *33 Marsh et al, 2013;Menon et al, 2010;Venhorst et al, 2014.…”
Section: (("Decision Making"[mesh] Not Shar*[tiab]) or ("Decision Supunclassified